Anti-trafficking professionals and institutionalized violence in Spain: An exploratory study - Clemente, M.; Sierra-Rodríguez, A.; Cairns, D. (Social Sciences, 2024)
In recent decades, an anti-trafficking legislative and policy framework has been developed in Spain, coupled with the funding of initiatives related to the protection of trafficked persons, especially women, largely carried out by faith-based and secular organizations. Using 25 interviews conducted with people employed in programmes targeting trafficked women in the Autonomous Community of Madrid, this article provides deeper exploration of this under-studied subject with a view to gaining a better understanding of the work experiences of professionals involved in these initiatives, with special attention paid to the challenges they face in enacting anti-trafficking activities while avoiding producing violence on assisted persons. The experiences of these professionals highlight that the neoliberal outsourcing of services to non-governmental organizations nevertheless contributes towards making anti-trafficking an apparatus in which violence materializes and reproduces. Significantly, this violence involves not only the people who are being assisted as trafficking victims but also some anti-trafficking professionals.